Methodological Concepts and Research Methods Used in Foreign Language Teaching - Yuliya Sakalova (Jan Dlugosz University, 2012)
This article examines and illustrates existing methodological concepts in FLT, their main features and techniques, as well as considers their effectiveness for a particular group of learners with their own problems in foreign language acquisition. The following methods have been analysed: the Grammar-Translation Method, the Audio-Lingual Method, the Direct Method and the Communicative Approach. The attention has also been paid to the problem of learning and translating culture-loaded words as one of the aspects in teaching a foreign language. Finally, our own research results in the ﬁ eld of foreign language acquisition are presented.